Fisheries community behaviour towards water quality of the Deket river, Lamongan district. Issue 1 (March 2021) - Saad, M; Milad, R M; Faiz, Y A A; Hikmah, N L
Abstract: The river as a water source is one of the natural resources which has a multipurpose function for life, livelihood and also aquaculture. The Deket River is one of the rivers in Lamongan Regency that has experienced a decline in water quality, due to contamination by domestic and industrial waste. This study aims to determine the behaviour, perceptions and attitudes of the fisheries community towards the quality of the waters in the Deket River, Lamongan Regency. This research uses descriptive quantitative and qualitative methods. This research was conducted at 3 stations and 3 sample points for observation of water quality. The lab test results show that the average value of 3 stations still has several parameters that exceed the maximum threshold and are classified as light pollution. Based on the multiple linear regression test, people's perceptions and attitudes about the decline in water quality affect fisheries community behaviour by 49%. Several water quality parameters caused by domestic and industrial waste have values above the maximum threshold, so they can be an indicator of degradation in water quality. The decline in water quality in the Deket River can affect the behaviour of the fisheries community around the riverbanks